Perianal Diseases in Pregnancy and After Childbirth: Frequency, Risk Factors, Impact on Women's Quality of Life and Treatment Methods - Bužinskienė, Diana; Sabonytė-Balšaitienė, Živilė; Poškus, Tomas (Frontiers in Surgery, 2022)
Hemorrhoids and anal fissures occur in about 40 percent of pregnant women and women during postpartum period. Usually they occur during the third trimester of pregnancy and 1-2 days after giving birth. Constipation during pregnancy, peri-anal diseases during previous pregnancy and childbirth, instrumental delivery, straining duration of more than 20 min, newborn weight of more than 3800 g are associated with hemorrhoids. Perianal diseases reduce the quality of life of both pregnant and postpartum women. In the absence of acute conditions, surgical treatment of hemorrhoids is delayed after pregnancy, childbirth and lactation. Thrombosed internal hemorrhoids and perianal thrombosis are to be treated in most instances conservatively by prescribing adequate pain relief, oral and topical flavonoid preparations.